Methods of accounting engineer-psychological factors in preparing the operators for aviation complexes - Казак, В. Н.; Казак, А. В. (Proceedings of National Aviation University (archive), 1999)
Considered are the methods of accounting engineer-psychological factors in preparing the operators for aviation complexes. Worked up is the structure of person as individuality